The Effect of Rias Banana Fiber Percentage as A Reinforcement of Polyester Matric Composite in The Efforts to Increase Waste Materials to Become a High Value Functional Material - Rahayu Mekar Bisono; Zulfa Khalida; Nila Nurlina (Universitas Trunojoyo Madura, 2019)
Along with the reduced use of metal in various materials, many new materials that have characteristics close to the metal have been developed for example in terms of tensile strength or other mechanical strength and have other advantages such as ease of manufacturing and low production costs. Composite is a material that is formed from a minimum of two materials and usually has different mechanical properties to get new properties that are better than the ingredients. Each composite produces different properties depending on the matrix filler, type of filler and reinforcing material used. Rias banana fiber and wood sawdust available in large quantities need to be utilized better, for example for composite materials. This research can facilitate development in other fields because it has criteria to reduce metal imports, increase local product content, and increase foreign exchange if the product is exported. This study also supports government programs to increase independence in making independent products. The results of this study indicate that variations in the composition of composites made from rias banana fiber and teak sawdust with an epoxy matrix affect the mechanical properties of the composite. Hardness value increases with increasing percentage of resin given. While the highest value of max strength is produced by composites with basic ingredients of 40% rias banana fiber, 20% teak sawdust and 40% epoxy. In this study it was concluded that the more resin given, the higher the composite hardness